2008
DOI: 10.1007/s10557-008-6130-y
|View full text |Cite
|
Sign up to set email alerts
|

A Single Intravenous sTNFR-Fc Administration at the Time of Reperfusion Limits Infarct Size—Implications in Reperfusion Strategies in Man

Abstract: A single administration of sTNFR-Fc at the time of reperfusion after myocardial infarction is able to limit infarct size and to reduce early LV diastolic dysfunction in rats. These findings suggest that intravenous neutralization of TNF-alpha during surgical cardiac reperfusion might improve the outcome of myocardial infarction in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Thus, they used a single intravenous injection of soluble TNF-α receptor at the time of reperfusion and they tried to find whether it could reduce the infract size and improve post-ischemic cardiac function in vivo in rats. They concluded that inhibition of increased TNF-α production by a single IV injection of sTNFR-Fc improved post-infract outcome in rats [25]. …”
Section: Inflammatory Markers and Atherosclerosis Progression – Link mentioning
confidence: 99%
“…Thus, they used a single intravenous injection of soluble TNF-α receptor at the time of reperfusion and they tried to find whether it could reduce the infract size and improve post-ischemic cardiac function in vivo in rats. They concluded that inhibition of increased TNF-α production by a single IV injection of sTNFR-Fc improved post-infract outcome in rats [25]. …”
Section: Inflammatory Markers and Atherosclerosis Progression – Link mentioning
confidence: 99%
“…TNF-α levels were found higher in patients suffering from heart failure [49]. In a variety of experimental MI models, the treatment with IL-1β [50], IL-6 [51] or TNF α [52]inhibiting agent showed positive effects on left LVEF and infarct size. Similarly, in our present study the involvement of proin ammatory cytokines decrease in SFN's cardioprotection was also demonstrated in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…Neutralization of TNF has also been recorded to have positive unintended consequences; patients with rheumatoid arthritis treated with anti‐TNF agents had a lower incidence of cardiovascular events and improved insulin resistance (Barnabe et al., 2011 ; Gonzalez‐Gay et al., 2006 ; Jacobsson et al., 2005 ; Kiortsis et al., 2005 ; van Eijk et al., 2009 ). Work with experimental animal models has shown that TNF neutralization is an effective therapeutic in heart disease and neurodegenerative diseases like Alzheimer's disease (Csiszar et al., 2007 ; Moe et al., 2004 ; Shamim & Laskowski, 2017 ; Toufektsian et al., 2008 ; Wolfe & Michaud, 2004 ). Thus, TNF inhibitors, along with other immune modulators, have possible prophylactic roles that we do not yet fully comprehend.…”
Section: Discussionmentioning
confidence: 99%